Optimización al mantenimiento de las estaciones de servicio de la empresa Surpetroil S.A.S. (2016)
For maintenance optimization in the company Surpetroil SAS it’s know the functioning of the company, its beginnings, its services and equipment. The current situation was diagnosed maintenance, maintenance schedules, resumes of equipment, inspection and calibration routines, maintenance service were analyzed, to analyze all this information and have a clear idea of how maintenance is performed. The information obtained was the basis for further basic formats maintenance; sheet, work request, work order and resume. Similarly systematic inspection programs, lubrication, adjustment and cleaning were redesigned. In addition, a program implementation plan maintenance for a period of three months was set.